Selektif Vastus Medial Obliquus Exercise Menurunkan Derajat Nyeri Dan Pencapaian Range Of Motion Pasien Dengan Patellofemoral Pain Syndrome - Putu Wira Kusuma putra; I Wayan Ari Antana; Ida Ayu Ageng Laksmi (Poltekkes Kemenkes Jakarta III, 2019)
Patellofemoral Pain Syndrome (PFPS) is pain in the front knee joint due to muscle imbalance especially weakness of the vastus medialis oblique muscle and the stiffness of the hamstrings leads to a patellar position shift to the lateral side (maltracking). Selective VMO exercise is one of conservative therapy to restore VMO muscle strength. The purpose of this study was to determine the effect of Selective Vastus Medial Obliquus Exercise on decreasing the degree of pain and attainment of Range Of Motion patients with PateloFemoral Pain Syndrome. The method of this research used pre experimental design with one group pre-post test design without group control. The number of samples is 13 respondents PFPS who meet the criteria of inclusion and exclusion with purposive sampling. Data were obtained from observation of difference of Visual Analogue Scale (VAS) and ROM (universal goniometer) pain score before (pre-test) and after (post-test) doing exercise therapy. All data were analyzed statistic using Wilcoxon Signed Ranks Test with significance value (p <0,05).. The result of this research shows that there is selective effect of Vastus Medial Obliquus Exercise on the decrease of pain degree with p value = 0.001 (α = 0,05) and attainment of Range Of Motion patient with flexy value p value = 0,039 (α = 0,05) p value = 0.001 (α = 0.05). Decreasing the degree of pain post selective VMO exercise and attainment full ROM showed strengthening of VMO muscle so patella returned to optimal tracking. Suggestion: Measurement of VMO and VL muscle strength can be done with EMG.